Potential of Ciplukan Leaf Extract (Physalis angulata L.) Against Streptococcus pneumoniae Growth in Vitro - Rakhman, Farizky; Widayati, Ratna; Turnip, Oktaviani Naulita; Fatmaria, Fatmaria; Hanasia, Hanasia (Poltekkes Kemenkes Gorontalo, 2025)
Pneumonia is a disease that infects the lungs, and antibiotics such as tetracycline show a high degree of resistance. Therefore, the use of alternative natural materials, such as ciplukan leaves (Physalis angulata L.), which the Dayak people commonly use to treat lung diseases, is necessary. This study aimed to prove that the extract of ciplukan leaves can inhibit Streptococcus pneumoniae by measuring the diameter of the clear zone and determining the Minimum Inhibitory Concentration (MIC). The extract was obtained by maceration using 96% ethanol, and then concentrations of 5%, 10%, 15%, 20%, and 25% were prepared. The positive control was levofloxacin 5 µg, and the negative control was DMSO 1%. The average inhibition zone diameters of the ciplukan leaf extract were 5% (0 mm), 10% (0.17 mm), 15% (0.45 mm), 20% (1.95 mm), 25% (2.67 mm). Antibacterial test using the disk diffusion method. From the Kruskal-Wallis and Mann-Whitney Post Hoc statistical test, a significance value of <0.05 was obtained. Therefore, There is an effect of ciplukan leaf extract on Streptococcus pneumoniae at concentrations of 15%, 20%, and 25%, with the MIC 15%.